Medical Oxygen Service Delivery and Utilization in Ethiopian Healthcare Facilities: Assessment of hospitals in Ethiopia - Belete, Alemayehu Berhanu; Kristinawati, Beti (Universitas Muhammadiyah Surakarta, 2025)
Ensuring reliable access to medical oxygen is critical to a quality healthcare system. A descriptive observational study was conducted over 6 months to examine the management and utilization of oxygen in hospitals across Ethiopia, focusing on facility and patient data. The study included 11 hospitals in 6 regions of Ethiopia, with data collection from emergency departments, ICUs, NICUs, pediatric and medical wards. Results showed that 36.36% of facilities had a functioning oxygen system, but less than half had a straightforward person in charge of oxygen and a standardized therapy flow. Meanwhile, 54.55% of facilities reported having medical personnel trained in oxygen therapy, although the number of trained staff varied. Incomplete oxygen prescriptions were shared, such as missing flow rates, SpO2, and monitoring frequency. However, patients who received oxygen therapy had a significantly higher recovery rate (66.23%) compared to patients who did not receive oxygen (21.43%). These findings indicate significant gaps in the availability and management of oxygen infrastructure and suboptimal oxygen administration and monitoring practices. A multifaceted approach is needed to remedy this, including improved functioning of oxygen plants, the appointment of dedicated oxygen attendants, standardized therapy protocols, broader training of medical personnel, and standardization of oxygen funding and costs.